AB0500 A Novel DNA-Peptide Complex Detects Anti-DSDNA Antibodies in SLE Sera. (15th July 2016) - Migliorini, P.; Panza, F.; Alcaro, M.C.; Petrelli, F.; Angelotti, F.; Pratesi, F.; Rovero, P.
Abstract : Background: The detection of anti-dsDNA antibodies is critical for the diagnosis and follow-up of SLE patients. The presently available assays are characterized by a non-optimal specificity (solid phase assays) or sensitivity (CLIF test). Objectives: To overcome the limits of CLIFT and solid phase chromatin assays, we explored the diagnostic potential of an assay based on plasmid DNA containing a highly bent fragment of 211 bp from Crithidia Luciliae microcircles, complexed with histone peptides. Methods: Electrically neutral complexes of PK201/CAT plasmid (PK) DNA and histone (H) 4 peptides were evaluated by electromobility shift assay. Complexes of H4 peptides and PK were absorbed to the solid phase to detect IgG antibodies in sera. Sera from 109 SLE patients, 100 normals and 69 disease controls (systemic sclerosis, Sjogren's syndrome, unclassified connective tissue disease) were tested. Results: H4 (14–34) containing the consensus sequence for DNA binding interacts with PK retarding its migration. H4 (14–34)-PK complexes were used to test sera by ELISA; inhibition assays show that sera react with epitopes present on DNA or on the complex, not on the peptide. Anti-H4-PK antibodies were detected in 56% SLE sera (more frequently in patients with skin or joint involvement) vs 12% disease controls; antibody titer is correlated with ECLAM score and anti-C1q antibodies, negatively with C3 levels. Anti-H4-PK antibodies compared with CLIFT and solid phase dsDNA assays display moderate concordance. Conclusions: The H4-PK assay is a simple and reliable test, endowed with high specificity and sensitivity, useful for the differential diagnosis and evaluation of disease activity of SLE patients. This assay increases the variety of anti-DNA antibodies that can be measured, complementing the assays currently used for the detection of anti-DNA antibodies. Disclosure of Interest: None declared